2015
DOI: 10.18632/oncotarget.2755
|View full text |Cite
|
Sign up to set email alerts
|

By downregulating TIAM1 expression, microRNA-329 suppresses gastric cancer invasion and growth

Abstract: Gastric cancer (GC) is one of the most common malignant tumors worldwide. Emerging evidence has shown that abnormal microRNAs (miRNAs) expression is involved in tumorigenesis. MiR-329 was previously reported to act as a tumor suppressor or oncogene in some types of cancer. However, its function in gastric cancer (GC) is unclear. Here, we found that miR-329 was down-regulated in GC compared with adjacent controls. Enforced expression of miR-329 inhibited proliferation, migration and invasion of gastric cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 44 publications
(39 reference statements)
3
75
0
1
Order By: Relevance
“…Increasing evidence has confirmed that loss of tumor suppressor genes is one of the crucial steps in the progression of cancers [19][20][21]. In our study, PAQR3 acted as a tumor suppressive gene in the tumorigenesis of LSCC.…”
Section: Discussionsupporting
confidence: 73%
“…Increasing evidence has confirmed that loss of tumor suppressor genes is one of the crucial steps in the progression of cancers [19][20][21]. In our study, PAQR3 acted as a tumor suppressive gene in the tumorigenesis of LSCC.…”
Section: Discussionsupporting
confidence: 73%
“…Recent studies showed that miRNAs play vital roles in regulating individual development, cell proliferation, metabolism, differentiation, invasion and migration in different disease [16-22]. A number of studies dispalyed that different miRNAs could increase or decrease cell apoptosis in OA, such as miR-149 and miR-30b [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…www.impactjournals.com/oncotarget Furthermore, our study displayed that miR-329 restricted cell growth by enhancing the level of several apoptosis prone proteins. Recently, it has been reported that miR-329 played tumor suppressive role by targeting different molecules in several cancers [18][19][20]. Due to miR-329 mainly inhibited cell growth in pancreatic cancer, in this study, we uncovered the miR-329-target network which was closely associated with cell proliferation and apoptosis by bioinformatic analysis.…”
Section: Discussionmentioning
confidence: 95%
“…MiR-329 was reported to promote tumor growth or metastasis in glioma, neuroblastoma and gastric cancer at decreased expression level [18][19][20]. However, the expression and function of miR-329 in pancreatic cancer is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation